Synthesis, Crystal Structure, and Conformation of Methyl 5-O-acetyl-5-cyano-6-deoxy-2,3-O-isopropylidene-β-l-gulofuranoside - Mičová, Júlia (Molecules, 2002)
Methyl 5-O-acetyl-5-cyano-6-deoxy-2,3-O-isopropylidene-β-l-gulofuranoside was prepared in high yield from methyl 6-deoxy-2,3-O-isopropylidene-α-d-lyxo-pentodialdo-1,4-furanoside. The configuration at the C5 atom was unambiguosly established by single crystal X-ray analysis of the corresponding 5-O-acetyl derivative. The conformation of the furanose and 1,3-dioxolane rings is also discussed.